A phase I/II study of sunitinib and intensive chemotherapy in patients over 60 years of age with acute myeloid leukaemia and activating FLT3 mutations - Fiedler, Walter; Kayser, Sabine (British journal of haematology, 2015)
Acute myeloid leukaemia (AML) with FLT3 mutation has a dismal prognosis in elderly patients. Treatment with a combination of FLT3 inhibitors and standard chemotherapy has not been extensively studied. Therefore, we instigated a phase I/II clinical trial of chemotherapy with cytosine arabinoside (Ara-C)/daunorubicin induction (7+3) followed by three cycles of intermediate-dose Ara-C consolidation in 22 AML patients with activating FLT3 mutations. Sunitinib was added at predefined dose levels and as maintenance therapy for 2 years. At dose level 1, sunitinib 25 mg daily continuously from day 1 onwards resulted in two cases with dose-limiting toxicity (DLT), prolonged haemotoxicity and hand-foot syndrome. At dose level −1, sunitinib 25 mg was restricted to days 1-7 of each chemotherapy cycle. One DLT was observed in six evaluable patients. Six additional patients were treated in an extension phase. Thirteen of 22 patients (59%; 8/14 with FLT3-internal tandem duplication and 5/8 with FLT3-tyrosine kinase domain) achieved a complete remission/complete remission with incomplete blood count recovery. For the 17 patients included at the lower dose level, median overall, relapse-free and event-free survival were 1·6, 1·0 and 0·4 years, respectively. Four out of five analysed patients with relapse during maintenance therapy lost their initial FLT3 mutation, suggesting outgrowth of FLT3 wild-type subclones.
Gesehen am 02.05.2017